2004
DOI: 10.1159/000082024
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Assisted Therapy Ameliorates Anhedonia in Schizophrenia Patients

Abstract: Background: Anhedonia, a component of the negative symptom dimension and a core phenomenon in schizophrenia, is associated with poor social functioning and is resistant to treatment. We tested the hypothesis that animal-assisted therapy (AAT) may improve anhedonia. Objective: To compare the effect of psychosocial treatment sessions in which a dog was an active participant (AAT) with comparable sessions without a dog, using a controlled protocol. Method: The hedonic tone of 10 chronic schizophrenia patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 47 publications
3
53
0
7
Order By: Relevance
“…A recent study by Nathans-Barel et al documented significant improvement in anhedonia for a group of adults with schizophrenia following 10 weeks of AAT when compared with the control group who were treated without AAT [26]. The patients who had the AAT sessions also showed improved use of leisure time and a trend toward improved motivation.…”
Section: Animal-assisted Therapymentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study by Nathans-Barel et al documented significant improvement in anhedonia for a group of adults with schizophrenia following 10 weeks of AAT when compared with the control group who were treated without AAT [26]. The patients who had the AAT sessions also showed improved use of leisure time and a trend toward improved motivation.…”
Section: Animal-assisted Therapymentioning
confidence: 97%
“…Following extensive literature review, we found no study to date that investigated the use of AAT for persons with stroke or aphasia. Despite the lack of research in AAT for persons with aphasia, numerous studies have been performed on the effects of AAT on other adult populations, such as residents of nursing homes [9][10][11][12]; patients in acute-care hospitals [13][14][15][16]; patients in intensive care units [17]; and adults with spinal cord injury [18], dementia [19][20], depression [21], psychiatric disorders [21][22][23], and schizophrenia [24][25][26].…”
Section: Animal-assisted Therapymentioning
confidence: 99%
“…Previous controlled studies of interaction with pets have shown significant decrease in depression during one week of hospitalisation among 230 psychiatric patients with psychotic and mood disorders (Barker and Dawson, 1998) and after two weeks of intervention with dolphins (Antonioli and Riveley, 2005). In a controlled pilot study on the effect of AAT on anhedonia among 10 schizophrenic patients, the Snaith-Hamilton Pleasure Scale showed significant improvement in the AAT group with a dog compared with the controls (Nathans- Barel et al, 2005). A few studies point to a reduction in depression among persons working with farm animals Hine et al, 2008;Ketelaars et al, 2001;Pedersen, 2011).…”
Section: Animals As Contributors To Reduced Arousal Anxiety and Depmentioning
confidence: 97%
“…Children with autism (Sams et al 2006b), people with HIV/AIDS (Allen et al 2000), and hospitalised patients with mental illnesses (Barak et al 2001;Kovacs et al 2004;Marr et al 2000;Nathans-Barel et al 2005) showed improved social functioning following the therapeutic introduction of animals.…”
Section: 62a Animal-assisted Therapy / Pet-facilitated Therapymentioning
confidence: 99%